A subtle review on the challenges of photocatalytic fuel cell for sustainable power production. (28th June 2021) - Mishra, Priyanka; Saravanan, Pichiah; Packirisamy, Gopinath; Jang, Min; Wang, Chuanyi
Abstract: The revolution in the arena of functional materials for the development of well advanced engineered photocatalyst can efficiently harness photon energy from a wide spectrum of electromagnetic radiation. These next-generation smart materials would be a spectacular approach in designing devices such as photovoltaic cells, photoelectrochemical cells, and photocatalytic fuel cells. Photocatalytic oxidation of water or wastewater for concurrent production of hydrogen and electric current has turned out as a principal concept for the construction of modern photocatalytic fuel cells (PFCs). Such PFCs mimics reverse photosynthesis process where electrical energy is generated from organic pollutants. In recent years many reviews on focusing the design, fabrication, and theoretical efficiency of the PFCs have been published. Hence the present review is aimed to unveil the wall-to-wall information starting from fundamentals spanning to working principles, structural configuration, electrochemical degradation of pollutants and photoelectrochemical properties, electron transport, thermodynamic behavior and columbic efficiency of studied PFCs. Graphical abstract: Image 1 Highlights: Challenges in the PFCs technology for sustainable power generation was examined. Discusses the relationship between efficacy -reactor design/photoactive materials. Impacts of key operational parameters on power generation were well considered. Electronic properties of photoanodes were reviewed for enhanced PFCs performance. Electrochemical/thermodynamic factors that impacts were also reviewed.